2015
DOI: 10.1007/s00167-015-3593-9
|View full text |Cite
|
Sign up to set email alerts
|

No difference in osteoarthritis after surgical and non-surgical treatment of ACL-injured knees after 10 years

Abstract: Prospective randomized study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 40 publications
(51 reference statements)
2
80
1
8
Order By: Relevance
“…ACL reconstruction is a commonly performed procedure that generally has excellent clinical outcomes. Numerous long term studies, however, have questioned its ability to prevent degenerative changes compared to non‐operative treatments . It has been suggested that abnormal kinematics after ACL reconstruction might be a factor predisposing the knee to these degenerative changes …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACL reconstruction is a commonly performed procedure that generally has excellent clinical outcomes. Numerous long term studies, however, have questioned its ability to prevent degenerative changes compared to non‐operative treatments . It has been suggested that abnormal kinematics after ACL reconstruction might be a factor predisposing the knee to these degenerative changes …”
Section: Resultsmentioning
confidence: 99%
“…Others have reported OA in more than 50% of patients 12–13 years after surgery . Despite advances in reconstructive techniques, early‐onset OA after ACL reconstruction remains a problem …”
Section: In Vivo Measurement Of Acl Graft Placement On the Femurmentioning
confidence: 99%
“…meniscus injuries) are important risk factors for developing osteoarthritis 22 . ACLR does alter the risk of early onset of osteoarthritis, compared to non-operative treatment 22,122 .…”
Section: Short-and Long-term Consequences After Acl Injurymentioning
confidence: 99%
“…An ACL reconstruction is the procedure that has been proven to improve knee stability and functional outcomes. Although there have been no clear benefits and prevention of osteoarthritic changes following ACL reconstruction [1,2], some studies have proven that this operative procedure can prevent these changes and subsequent meniscal injuries [3,4].…”
Section: Introductionmentioning
confidence: 99%